Mekanisme Aus Pahat Putar pada Pemesinan Magnesium AZ31 - Ibrahim, Gusri Akhyar; Harun, Suryadiwansa (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Magnesium alloy is one of the most popular light material which was used in biomedical. Magnesium alloy is very light, resistant to corrosion and good biocompatible. However, magnesium alloy is flammable, so it is effortless to burn. This research investigated the wear mechanism at the edge rotary cutting tool. The cutting tool used in this experiment is carbide insert with a diameter of 16 mm. Pressured cooling air was used to reduce wear progression. The cutting parameters selected were workpiece speed at 80, 120 and 180 m/min, feed rate at 0.10, 0.15 and 0.20 mm/rev., tool speed at 25, 50 and 75 mm/min, and constant depth of cut at 0.3 mm. Tool wear and wear mechanism of the cutting tool were measured by using a microscope with particular magnification. Maximum wear on the carbide cutting tool was 0.449 mm, which was achieved at the end of tool life. Dominant wear mechanism occurred at the cutting tool was abrasive wear. Some scratches were observed at the edge of the tool as a result of hard particles. Another wear type that occurred was crater wear at the top area of the insert. The wear on the cutting tool was due to the excessive heat generated during the machining process, which was due to friction between the cutting tool and workpiece material.